Variability of heart rate of elite wrestlers in conditions of artificial dehydration of the organism - Korobeynikov, G. V.; Korobeynikova, L. G.; Ludanov, K. V.; Mischenko, V. S.; Ludanov, D. R. (Ukrainian Journal of Medicine, Biology and Sport, 2020)
The purpose of the work was to study the variability of heart rhythm in fighters who used artificial dehydration of the body. Material and methods. Statistical and spectral analysis of heart rate variability were used in the study. We examined 14 elite athletes, members of the national team of Ukraine in Greco-Roman wrestling, aged 21-25 years. The first group (main) consisted of athletes who use artificial dehydration of the organism (n = 7). Another group (control) consisted of athletes who did not use artificial dehydration of the body (n = 7). Results and discussion. The obtained results showed that the wrestlers who did not use artificial dehydration had a higher level of tension in heart rhythm regulation compared to wrestlers who used dehydration. This is confirmed by the high SDNN values for wrestlers with artificial dehydration, compared with the other group. This fact indicates the presence of more intense regulation of the heart rate in athletes who do not use that artificial dehydration. At the same time, we found out that the Mo indicator was significantly higher in wrestlers with artificial dehydration, than in wrestlers without artificial dehydration of the body. This indicates the activation of humoral regulation of the sinus node of the heart in the process of weight-losing. The presence of large AMo values in wrestlers without artificial dehydration compared with fighters who used artificial dehydration indicates activation of the sympathetic department of the autonomic nervous system. Similar results were obtained when studying the spectral characteristics of heart rate variability. The main group athletes had increased HF values which illustrate an increase in parasympathetic influences. At the same time, the low-frequency range of heart rate fluctuations was lower in athletes who did not use artificial dehydration. These results indicate the optimal activation of the sympathetic division of the autonomic nervous system in fighters who did not use artificial dehydration. Conclusion. There is a change in both temporal and spectral indicators of heart rhythm in athletes using artificial dehydration of the body. Indicators of SDNN, RMSSD, pNN50, LF, HF were significantly higher, and LF / HF lower than the corresponding indicators of fighters who did not use artificial dehydration of the body (control group), indicating increased activation of neurohumoral centers and parasympathetic nervous system. Wrestlers who did not use artificial dehydration had a higher level of heart rate regulation than wrestlers who used it. Humoral and sympathetic links of regulation were activated with increasing tension of the autonomous regulation system of the heart's rhythm as fighters who do not use artificial dehydration.